RADI-05. FRACTIONATED TREATMENT OF BRAIN METASTASES WITH GAMMA KNIFE ICON. (12th August 2019) - Mendel, Jameson; Patel, Ankur; Patel, Toral; Timmerman, Robert; Dan, Tu; Nedzi, Lucien; Wardak, Zabi
Abstract: PURPOSE/OBJECTIVE(S): Stereotactic radiosurgery with Gamma Knife is a common treatment modality for patients with brain metastasis. The Gamma Knife ICON allows for immobilization with an aquaplast mask, permitting fractionated treatments. We describe one of the first experiences utilizing this technique with brain metastasis and evaluate outcomes. MATERIALS/METHODS: From June 2017 to November 2018, 29 patients with 43 separate intracranial lesions were treated with fractionated stereotactic radiotherapy using the gamma knife ICON at a single institution. Patients received between 20–30 Gy in 3–5 fractions with no margin over the course of 5 to 23 days. Local control was physician assessed. Local failure over time was modeled using cumulative incidence; lesions were censored at last radiographic follow up. RESULTS: Median tumor volume and prescription isodose was 7.7 cm 3 (range 0.3–43.9) and 50% (range 40–65), respectively. Median radiographic follow-up was 7 months and median survival was 9 months. Radiation necrosis occurred in 3/3 patients treated with 27 Gy in 3 fractions, one requiring therapeutic resection. Incidence of local failure for all treated lesions was 9% at 1 year. Tumor volume >7 cm 3 was associated with local failure on univariate analysis (p=0.025). 100% (2/2) lesions treated with 20 Gy in 5 fractions developed local recurrence. CONCLUSION: Fractionated stereotactic radiotherapy with the Gamma Knife ICON provides excellent local control for small and large brain metastases with minimal toxicity. Tumors >7 cm 3 should receive at least 30 Gy in 5 fractions for optimal control. Treatment with 27 Gy in 3 fractions appears to have high rates of treatment related toxicity and should be avoided.